Prosedur Pelaksanaan Strategi Pembelajaran Ekspositori - Safriadi Safriadi (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2017)
Expository learning strategy is a learning strategy emphasizes the process of verbal material delivery from a teacher to a group of students with the intention that students can master the subject matter optimally. In expository learning, the teacher presents the material in a well-prepared, systematic and complete form so that the students just listen and digest it regularly and orderly. In the use of an expository learning strategy there are several principles, namely: goal-oriented principles, communication principles, preparedness principles and sustainable principles. Based on these principles, teachers can apply the procedures to be implemented in expository learning, formulate goals to be achieved, master the subject matter well, recognize the terrain and various things that can affect the process of teaching delivery. Teachers can apply some steps in the implementation of expository strategies, namely: preparing students to receive lessons, preparing subject material that is easily captured and understood by students. Next connect the subject matter with the student experience, understand the essence of the lesson material that has been presented and the last step is to show students ability after they listen to the explanation from the teacher.